Durability of COVID-19 humoral immunity post infection and different SARS-COV-2 vaccines - Fayhan Alroqi; Tlili Barhoumi; Emad Masuadi; Maysa Nogoud; Modhi Aljedaie; Ahmad Selah Abu-Jaffal; Maha Bokhamseen; Myaad Saud; Maumonah Hakami; Yaseen M. Arabi; Amre Nasr (Elsevier, 2024)
Background: The global challenge posed by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has been a major concern for the healthcare sector in recent years. Healthcare workers have a relatively high risk of encountering COVID-19 patients, making protective immunity against SARS-CoV-2 is a priority for them. This study aims to evaluate the longitudinal measurement of SARS-CoV-2 IgG spike protein antibodies in healthcare workers (HCWs) after COVID-19 infection and after receiving the first and second doses of SARS-CoV-2 vaccines, including Pfizer-BioNTech (BNT162b2) and Oxford-AstraZeneca (AZD1222). Methods: This longitudinal cohort study involved 311 healthcare workers working in two tertiary hospitals in Saudi Arabia. All participants were followed between July 2020 and July 2022 after completing the study questionnaire. A total of 3 ml of the blood samples were collected at four intervals: before/after vaccination. Results: HCWs post-infection had lower mean SARS-CoV-2 IgG levels three months post-infection than post-vaccination. 92.2% had positive IgG levels two weeks after the first dose and reached 100% after the second dose. Over 98% had positive antibodies nine months after the second dose, regardless of vaccine type. The number of neutralizing antibodies decreased and was around 50% at nine months after the second dose. Conclusion: The results show different antibody patterns between infected and vaccinated HCWs. A high proportion of participants had positive antibodies after vaccination, with high levels persisting nine months after the second dose. Neutralizing antibodies decreased over time, with only about 50% of participants having positive antibodies nine months after the second dose. These results contribute to our understanding of immunity in healthcare workers and highlight the need for the continuous monitoring and possible booster strategies.